Information System for Personnel at the South Sorong District Regional Personnel Agency Office - Ummiati Rahmah; Mahmud Mustapa; Wulansari, Lusiana; Mansyur; Harpa Pali (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
Due to the increasing complexity of globalization and technological advancements, the adoption of HRIS (Human Resource Information System) has become a key priority for government bodies and similar organizations. HRIS plays a vital role in effectively managing the workforce, particularly in the public sector. This research aims to enhance the efficiency of personnel data management processes in South Sorong Regency. The primary focus is on ensuring the security of employee data storage. Extreme Programming is utilized as the system development method, encompassing design, development, coding, and testing stages. PHP is chosen as the programming language, with a MySQL database for data storage. The black box testing technique is employed to guarantee system functionality and reliability. The implementation of this application demonstrates smooth operation, with testing yielding a high satisfaction rate among respondents at 93%. Consequently, the system is deemed functionally sound in delivering the intended outcomes.